Robertsonian rearrangements in the genome of the azure damselfish, Chrysiptera hemicyanea (Perciformes, Pomacentridae) - Nuntaporn Getlekha; Kamika Sribenja (Caryologia, 2025)
Cytogenetic studies on the azure damselfish, Chrysiptera hemicyanea (Weber, 1913), revealed a karyotype with 2n = 31 chromosomes (17 metacentric, 2 submetacentric, and 14 telocentric; FN = 52). The study found Robertsonian polymorphisms, which involve small heterochromatic regions at the centromeres. Nucleolar organizer regions (NORs) were observed near the ends of the long arms on the large metacentric chromosome pair (pair 2). FISH analysis, which detects specific DNA sequences, revealed notable variability in the distribution of ribosomal DNA (5S and 18S rDNAs) along the chromosomes. Specifically, the 18S rDNA was located at the ends of the long arms on the large metacentric chromosomes (pair 2), while the 5S rRNA genes were found near the centromere of another large metacentric chromosome pair (pair 3). The analysis also showed that repetitive DNA sequences (CA)15, (GA)15, and (CAA)10 were spread across the subtelomeric and telomeric regions of various chromosomes. The study suggests that the structure of the karyotype and chromosome number are linked to the Robertsonian rearrangements observed, highlighting their significant role in the evolutionary changes in the karyotype of the genus Chrysiptera.